Assessing stroke recurrence in sICAS: a study on mCSVD score and culprit plaque magnetic resonance characteristics - Ren, Kaixuan; He, Juan; Zhu, Li; Gu, Yue; Qu, Hang; Zhao, Yi; Wang, Wei (Frontiers in Neurology, 2024)
BackgroundRecurrent ischemic stroke in patients with symptomatic intracranial atherosclerotic stenosis (sICAS) can be attributed to two main causes: intracranial atherosclerotic stenosis (ICAS) and cerebral small vessel disease (CSVD). This study investigates the potential associations between stroke recurrence and the modified cerebral small vessel disease (mCSVD) burden score, as well as the characteristics of culprit plaques related to intracranial artery high-resolution vessel wall imaging (HR-VWI).MethodsA total of 145 patients presenting sICAS underwent intracranial artery HR-VWI and routine cranial MRI at two large Chinese hospitals from December 2019–2022 were participants of this retrospective analysis. Standard MRI scans were used to calculate the mCSVD score. Following a 12-month observation period, the patients were categorized into two distinct groups depending on whether or not they experienced a subsequent stroke.ResultsWithin 12 months, 32 patients experienced stroke recurrence. The recurrence group’s mCSVD score was higher compared to the non-recurrence group (p < 0.001). Their luminal stenosis and culprit plaque thickness and burden were also higher (p < 0.05). Additionally, higher rates of diabetes, T1WI hyperintensity of culprit plaques, and significant plaque enhancement were observed in the recurrence group (p < 0.05). The adjusted Cox regression model indicated that the mCSVD score (HR = 1.730, 95% CI 1.021–2.933, p = 0.042) and T1WI hyperintensity of the culprit plaque (HR = 6.568, 95% CI 1.104–39.059, p = 0.039) remained significantly independent risk variables. The combination of the mCSVD score and T1WI hyperintensity of the culprit plaque demonstrated the highest efficacy in predicting stroke recurrence (z = 2.678, p < 0.05).ConclusionThe mCSVD score, associated with T1WI hyperintensity of culprit plaque, effectively predicts stroke recurrence and can be easily obtained, offering high clinical value.